Fasilitas Rumah Creative dengan Pendekatan Arsitektur Biophilic di Desa Canggu - I Komang Winata Tri Aditya; Ni Putu Ratih Pradnyaswari Anasta Putri; I Nyoman Gede Mahaputra (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
The creative industry is an industry that has intellectual property in it, with creative ideas poured into a work by channeling interests and talents in a creative house. Collaboration in producing works is indispensable for the creation of a trade and financial ecosystem in this industry. The application of the concept of biophilic in the collaboration is expected to provide not only between humans and humans but also involves the surrounding environment to make all human sensors usable and can have a good influence on the user's psychology, apart from considering the closeness of humans and the environment, biophilic can also stimulate the surrounding environment. to be better because previously there was a shift in the ecosystem in the area used as the design site. The polluted environment is also a design consideration for how buildings can respond to environmental problems.